Source Level of Antarctic Blue and Fin Whale Sounds Recorded on Sonobuoys Deployed in the Deep-Ocean Off Antarctica - Miller, Brian S.; Calderan, Susannah; Leaper, Russell; Miller, Elanor J.; Širović, Ana; Stafford, Kathleen M.; Bell, Elanor; Double, Michael C. (Frontiers in Marine Science, 2021)
The source levels, SL, of Antarctic blue and fin whale calls were estimated using acoustic recordings collected from directional sonobuoys deployed during an Antarctic voyage in 2019. Antarctic blue whale call types included stereotyped song and downswept frequency-modulated calls, often, respectively, referred to as Z-calls (comprising song units-A, B, and C) and D-calls. Fin whale calls included 20 Hz pulses and 40 Hz downswept calls. Source levels were obtained by measuring received levels (RL) and modelling transmission losses (TL) for each detection. Estimates of SL were sensitive to the parameters used in TL models, particularly the seafloor geoacoustic properties and depth of the calling whale. For our best estimate of TL and whale-depth, mean SL in dB re 1 μPa ± 1 standard deviation ranged between 188–191 ± 6–8 dB for blue whale call types and 189–192 ± 6 dB for fin whale call types. These estimates of SL are the first from the Southern Hemisphere for D-calls and 40 Hz downsweeps, and the largest sample size to-date for Antarctic blue whale song. Knowledge of source levels is essential for estimating the detection range and communication space of these calls and will enable more accurate comparisons of detections of these sounds from sonobuoy surveys and across international long-term monitoring networks.